On the value of meta‐research for early career researchers: A commentary - Nicholas Fabiano; Arnav Gupta; Jess G. Fiedorowicz; Marco Solmi (Wiley, 2024)
Abstract Meta‐research, also known as "research on research" is a field of study that investigates the methods, reporting, reproducibility, evaluation, and incentives along the research continuum. Meta‐research literacy is imperative to ensure high quality, transparent and reproducible primary data or meta‐research products. In this commentary, we propose that early career researchers should be trained in meta‐research as a foundation to develop a deeper understanding of the research process and ability to appraise the research literature and design high‐quality original studies, irrespective of their chosen field of study. We discuss the importance of meta‐research and open science from the perspective of an early career trainee, highlighting essential areas for growth and obstacles one may encounter.